From left to right: Gori, Croce, Borghetti, Milano. Photo made in the prison of Lugano. Dedication from Milano to M. Nettlau - Brunel, G.,
From left to right: Gori, Croce, Borghetti, Milano. Photo made in the prison of Lugano. Dedication from Milano to M. Nettlau.